Comparison of the risk of obesity in the FTO rs9939609 genotype in a multiethnic group in Asia systematic review and meta-analysis - Pratiwi, Donna; Sidartha, Miko; Wiyarta, Elvan; Agustinus Harimawan, I Wayan; Lestari, Ni Made Dwi Asti; Kim, Bonglee; Taslim, Nurpudji Astuti; Tallei, Trina Ekawati; Nurkolis, Fahrul; Syahputra, Rony Abdi (Frontiers in Medicine, 2025)
AimThis study aims to examine the comparative risk of obesity in the FTO rs9939609 genotype in multiethnic groups in Asia, considering that obesity has become a global disease.Data synthesisData searches were carried out in several electronic databases: PubMed, Scopus, Google Scholar, ScienceDirect, ClinicalTrials.gov and NCBI. The search involved a combination of keywords related to genetics and obesity risk. Pooled Odds Ratio (POR) with 95% CI was calculated based on the pooled data. Review Manager (RevMan) 5.4.1 were used to analyze the data.ResultsFrom 18 studies, the results of the dominant genetic model AA vs. TT showed POR 95%Cl = 1.95 (1.36–2.80); p < 0.00001, in AA vs. TA genetic recessive model, POR 95%Cl =1.31 (1.07–1.60); p = 0.002, then the final model of TA vs. TT codominance genetic model obtained POR 95%Cl = 1.52 (1.04–2.23); p < 0.00001. The overall risk of bias was low.ConclusionFrom this research, it was found that there was a comparison of the genotype that had a higher risk of obesity, namely the AA genotype in multiethnic groups in Asia.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=546434.